Astragali Radix and its compound formononetin ameliorate diesel particulate matter-induced skin barrier disruption by regulation of keratinocyte proliferation and apoptosis. (10th January 2019) - Nguyen, Ly Thi Huong; Nguyen, Uy Thai; Kim, Yeoun-Hee; Shin, Heung-Mook; Yang, In-Jun
Abstract: Ethnopharmacological relevance: Astragali Radix (AR), the root of Astragalus mongholicus Bunge, is widely applied in traditional medicine to promote skin health and tissue regeneration. Aim of the study: This study investigated the effects of AR and its active compound, formononetin (FMT), on skin barrier defects in keratinocytes exposed to diesel particulate matter (PM). Materials and methods: HaCaT cells and three-dimensional (3D) human skin reconstructed model were pre-treated with AR (50, 100 μg/ml) and FMT (30, 50 μM), then treated with PM (200 μg/ml). Results: AR and FMT significantly enhanced the expression of Keratin (KRT) 16 in PM stimulated HaCaT cells. PM increased p53 and Bax expression as well as the subsequent cleavage of caspase 3 and PARP in HaCaT cells, while this was inhibited by AR and FMT treatment. In vitro studies using the PM stimulated 3D human skin reconstructed model revealed that AR and FMT increased the expression of KRT 16 and KRT 17. Histological examination of the 3D human skin reconstructed model showed that AR and FMT up-regulated the expression of Ki67, but down-regulated the expression of cleaved caspase 3. Both AR and FMT significantly inhibited phosphorylation of ERK, but not JNK and p38 MAPK in PM stimulated HaCaT cells. Conclusions: These results suggest that AR and FMT act as anti-pollution agents and alleviate PM induced skin barrier defects through regulation of apoptosis and proliferation in keratinocytes. Graphical abstract: